Earth! my first 4.54 billion years - McAnulty, Stacy; Litchfield, David (New York Henry Holt and Company, 2017)
This lighthearted nonfiction picture book about the formation and history of the Earth is told from the perspective of the Earth itself.
Includes bibliographical references.
Junior Library Guild
AD 540
Grades K-2.
Ages 5-7.
A Junior Library Guild selection (JLG)
Keywords: Life -- Origin; Continents; Life -- Origin; Geological time; Continents; Life -- Origin -- Juvenile literature; Geological time -- Juvenile literature; Continents -- Juvenile literature; Earth -- Age; Earth (Planet) -- Age; Earth (Planet) -- Age -- Juvenile literature